Resilience and Recovery: Clustering International Tourism Trends in Indonesia Amidst COVID-19 - Rasyidi, Mohammad Arif (Sustainability and Social Impact, 2024)
This study presents a hierarchical clustering analysis of international tourism to Indonesia, examining the shifts in tourist volumes from various countries during the pre-pandemic, pandemic, and post-pandemic periods. Utilizing the agglomerative method with Euclidean distance and Ward linkage, the research identifies 13 distinct clusters, each reflecting unique patterns of tourism volume change. The analysis reveals the resilience of the tourism industry, with some clusters demonstrating remarkable recovery, surpassing pre-pandemic levels, while others indicate a more gradual return to normalcy. The findings offer significant implications for tourism policy and management, suggesting the need for targeted strategies to foster recovery and growth. The study also underscores the importance of crisis management and preparedness, highlighting the role of data analytics in strategic decision-making within the tourism sector. Future research directions include incorporating additional variables, conducting longitudinal studies, and exploring the relationship between tourism and public health measures.